Multi-Threading Elliptic Curve Cryptosystems. - Kanniah, Uma S.; Samsudin, Azman (2007)
Elliptic Curve Cryptosystems (ECC) is being widely used in cryptographic systems due to its unique security features. In many cases, ECC had also been crafted onto specialized processor for performance reason. However, building a specialized ECC processor is not only time consuming but also costly.